The grifters [videorecording (DVD)] - Frears, Stephen; Cusack, John, 1966-; Huston, Anjelica; Bening, Annette; Bernstein, Elmer; Thompson, Jim, 1906-1977 (Miramax Films : Distributed by Buena Vista Entertainment, 2002)
Three con artists walk on the razor's edge of life. Lilly has decided it's time to get out, and wants her son out, too. But Roy has fallen for sleek Myra, who wants him for her partner.